Pengaruh Solidaritas Sosial Karang Taruna dalam Program Pengangkutan Sampah terhadap Kepuasan Masyarakat Desa Kesamben Kabupaten Tuban - Munti Kurnia Ningsih; Alan Sigit Fibrianto (J-MAS (Jurnal Manajemen dan Sains), 2023)
The garbage collection program has been running since September 2021 with the enthusiasm of the Youth Organization of Kesamben Village. The purpose of this study was to obtain information related to the significant influence of Karang Taruna Social Solidarity. This study uses a quantitative approach with a simple linear regression method and also Pearson Correlation. The sampling technique used was purposive sampling. The data used is primary data obtained through distributing questionnaires using the Google form. The results of the analysis obtained the equation Å· = -17.09 + 1.2240x which means that if the Youth Organization Social Solidarity variable (X) has increased by 1 unit, the y variable has increased by 1.2240. Based on r table with a confidence level of 0.05 (r table for 75 subjects with a 5% confidence level is 0.191), it is understood that r count > r table (0.882 > 0.191). So it can be concluded that there is a significant relationship between social solidarity and community satisfaction. The T-test obtained a p-value <Î± = 0.05 for variable X which can be interpreted as Karang Taruna Social Solidarity (X) has a significant effect on community satisfaction (Y).